An Overview of Complications and Treatment Strategies in Periocular Dermal Fillers: A Literature Review - Aleksandra Ciesielska; Aleksandra Sieradzka; Krzysztof Szerej; Alicja Kot; Marta Wojtczak; Natalia Myśliwiec; Adrian Różycki; Michał Pniak; Paweł Miklis; Maciej Mawlichanów (Quality in Sport)
Introduction:  The dermal filler market is a continuously expanding billion-dollar industry with the number of performed injections growing concurrently with the amount of post-injection complications. Most adverse events are mild and resolve spontaneously. Ischemic complications due to accidental intra-arterial filler injection may lead to skin necrosis and even irreversible vision loss.